Midwifery Facilitation: Exploring the Functionality of Labor Discomfort. Issue 3 (September 2016) - Sanders, R.
Abstract : ( Birth. 2015;42(3):202–205) Currently, only 36% of labors in the United Kingdom are performed without anesthesia. This commentary explores the increasing trend of women choosing to medicate during labor. The practice of midwifery focuses on supporting women through the birthing process. Putting the emphasis on facilitating labor—making it as easy, not as painless, as possible—could reduce the reliance on pharmacological methods of anesthesia. As the perception of how painful labor is can be altered by the woman's labor experience, changing the language used in describing labor pain could help alter the cultural perception of it.